2020
DOI: 10.1007/s00213-020-05496-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-HT2C, 5-HT1A receptor challenges and modafinil on the initiation and persistence of gambling behaviours

Abstract: Rationale Problematic patterns of gambling are characterised by loss of control and persistent gambling often to recover losses. However, little is known about the mechanisms that mediate initial choices to begin gambling and then continue to gamble in the face of losing outcomes. Objectives These experiments first assessed gambling and loss-chasing performance under different win/lose probabilities in C57Bl/6 mice, and then investigated the effects of antagonism of 5-HT 2C R with SB242084, 5-HT 1A R agonism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Within the two populations (i.e. dopamine agonist reports and antipsychotic reports, see Supplementary Material-Table S2 and S3), ICD reports were characterized by a significantly higher proportion of men (50.58% vs 47.56% in antipsychotics; 59.90% vs 39.46% in dopamine agonists) and younger age (median[Q1-Q3] = 42 years vs 50 in antipsychotics; 56 [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] vs 66 in dopamine agonists). Lower proportions of deaths (2.05% vs 12.20% in antipsychotics; 2.42% vs 7.62% in dopamine agonists) and higher of disability (9.60% vs 1.95%; 4.42% vs 2.26%) were also reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the two populations (i.e. dopamine agonist reports and antipsychotic reports, see Supplementary Material-Table S2 and S3), ICD reports were characterized by a significantly higher proportion of men (50.58% vs 47.56% in antipsychotics; 59.90% vs 39.46% in dopamine agonists) and younger age (median[Q1-Q3] = 42 years vs 50 in antipsychotics; 56 [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] vs 66 in dopamine agonists). Lower proportions of deaths (2.05% vs 12.20% in antipsychotics; 2.42% vs 7.62% in dopamine agonists) and higher of disability (9.60% vs 1.95%; 4.42% vs 2.26%) were also reported.…”
Section: Resultsmentioning
confidence: 99%
“…The onset of ICDs was earlier for antipsychotics (median [Q1-Q3] = 31 [1-366] days, on 1871 available time to onset data) than for dopamine agonists (214 days, on 662 available time to onset data). Dopamine-agonist related ICDs, compared to antipsychotic-related ICDs, also had higher contribution by men (59.90% vs 50.58%) and older people (56 [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] vs 42 years old). Finally, the 254 ICD cases recording the use of both dopamine agonists and antipsychotics (Table S4) shared the characteristics of ICDs occurring with dopamine agonists (men 60.00%, age 56 ), but were more similar to ICDs occurring with antipsychotics in the lawyer contribution (15.29%) and the reported disability rate (8.27%), and the reported hospitalization rate (42.13%) was substantially higher than when developing ICDs with dopamine agonists (16.84%) or antipsychotics (32.50%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is coherent with the finding, in Parkinson’s disease, that ICDs are associated with an increased release of dopamine in the ventral striatum ( Martini et al, 2018 ), which opposes the prevailing hypothesis of a primary role related to the exogenous dopaminergic activity. Interestingly, different studies have already demonstrated 5-HT1A–induced impulsivity and addiction in mice ( Humby et al, 2020 ; Chu et al, 2021 ) and investigated the relationship between impulsivity and 5-HT1A polymorphisms in humans ( Benko et al, 2010 ; Stamatis et al, 2020 ). Furthermore, 5-HT1A agonists such as buspirone and vortioxetine may cause impulsive-compulsive behaviors in rats ( Liu et al, 2004 ; Lu et al, 2013 ; Martis et al, 2021 ), and a 5-HT1A partial agonist (tandospirone) may result in reduced impulsivity in rats because of its 5-HT1A antagonistic activity ( Ohmura et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it will be fruitful to explore novel paradigms that can capture key cognitive processes that may be involved in between-session and within-session loss-chasing. For instance, recent work developed a new behavioural task that allowed rats to initiate gambling (which might be related to between-session loss-chasing) or continue gambling after starting (which might be related to within-session loss-chasing), and showed that these two decisions have dissociable neurochemical underpinnings (Humby et al, 2020). An interesting avenue for future research can be to examine whether the decisions to initiate or continue gambling in such tasks can be related to loss-chasing between-and within-session among gamblers.…”
Section: Relationships Between Between-session and Within-session Los...mentioning
confidence: 99%